PEMANFAATAN RUANG TERBUKA HIJAU PADA BANGUNAN SIRING BANTARAN SUNGAI MARTAPURA KOTA BANJARMASIN - Edwin Hasymi (Lambung Mangkurat University Press, 2019)
Open space is a space that is planned as a place for various social activities. Green open space created on the banks of the siring Jl. Piere Tendean is a city park that is free of building land. However, a building that has four floors called Menara Pandang has been built in this area where there should be no building at all. The Tower of View building is located in the Piere Tendean City Tourism Park in the city of Banjarmasin. The purpose of this research is to examine the extent of the feasibility of the View Tower. This research is based on the main regulations of a facility or building asset that can be built as an exception where there should be no building at all. Analysis of the legal aspects has been carried out based on regulations. And for the economic aspect, the analysis is carried out with a benefit value analysis (BCR) and a rate of return analysis (ROR). The results of the study provide that Menara Pandang, which stands at that location, is in conflict with several regulations. However, an analysis of economic aspects shows that this building is profitable and beneficial. Further research is recommended to consider the impact not only of the user but also the manager and the entire community around this facility.